Vincristine-induced peripheral neuropathic pain and expression of transient receptor potential vanilloid 1 in rat - Terumasa Chiba; Yusuke Oka; Hiroya Sashida; Toshie Kanbe; Kenji Abe; Iku Utsunomiya; Kyoji Taguchi (Elsevier, 2017)
The clinical anti-cancer efficacy of vincristine is limited by the development of dose-dependent peripheral neuropathy. Up-regulation of transient receptor potential vanilloid 1 (TRPV1) is correlated with peripheral neuropathy following anti-cancer drug treatment. To analyze the contribution of TRPV1 to the development of vincristine-induced mechanical allodynia/hyperalgesia, TRPV1 expression in the rat dorsal root ganglion (DRG) was analyzed after vincristine treatment. Mechanical allodynia/hyperalgesia was tested with von Frey filaments 14 days after intraperitoneal administration of 0.1 mg/kg vincristine in rats. TRPV1 expression in DRGs following vincristine treatment was assessed with western blot analysis and in situ hybridization histochemistry. Vincristine-induced mechanical allodynia/hyperalgesia after day 14 was significantly inhibited by the TRP antagonist ruthenium red (3 mg/kg, s.c.) and the TRPV1 antagonist capsazepine (30 mg/kg, s.c.). Vincristine treatment increased the expression of TRPV1 protein in DRG neurons. In situ hybridization histochemistry revealed that most of the TRPV1 mRNA-labeled neurons in the DRG were small in size. Immunohistochemistry showed that isolectin B4-positive small DRG neurons co-expressed TRPV1 protein 14 days after treatment. These results suggest that vincristine treatment increases TRPV1 expression in small DRG neurons. TRPV1 expression may contribute to the development of vincristine-induced painful peripheral neuropathy.